Hospitality work of the Bethlehemite in «Los Barbones» and the existence of medicinal plants in «El abad de Lunahuaná» in Ricardo Palma’s Tradiciones peruanas - Rosas Carbajal, Josselyn Yessenia (2020)
This article will analyse the existence of medicinal plants and the hospital work of the Bethlehemites, both themes found in the stories «El abad de Lunahuaná» and «Los Barbones» respectively. These texts form part of Tradiciones peruanas, a famous work by Ricardo Palma which was written as a result of his historical research, based on documents and also on oral traditions to which he introduced some fictional elements. Through this article we are interested in promoting university research, especially with regard to the use of medicinal plants, promoting their benefits and importance in the field of medicine up to the current day. It also seeks to highlight the active participation of the religious order of the Bethlehemites in the practice of medicine, both in their hospital work, dedicated to patient care, and in their knowledge in the area of pharmacology, generating a relationship between the past and the present through these stories.